2018
DOI: 10.1177/1461355718814852
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors as predictors of readiness to combat crime among police officers in Osun State Command, Nigeria

Abstract: The increasing crime rate and apparent reduction in combatting crime by law enforcement agencies in Nigeria, particularly the Nigerian Police, deserve attention from a psychological point of view. This study examined the extent to which locus of control and emotional intelligence (EI) predict readiness to combat crime among police officers in Osun State Police Command, Nigeria. The study used primary data embedded in a descriptive survey design. A multistage sampling technique was adopted to obtain data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A complex working environment is inclined to stir strong feelings of organizational dismay and even injustice, causing a vast array of undesirable outcomes. Officers may feel devalued, leading to doubt about their self-worth (Ayinde & Ayegun, 2018). Scholars also pointed out that Nigeria officers commit to their organization because of economic reasons, rather than having affection for the police department or work, contributing to the widespread problem of police corruption (Aremu et al, 2011).…”
Section: Predicting Organizational Commitment Among Police Officersmentioning
confidence: 99%
“…A complex working environment is inclined to stir strong feelings of organizational dismay and even injustice, causing a vast array of undesirable outcomes. Officers may feel devalued, leading to doubt about their self-worth (Ayinde & Ayegun, 2018). Scholars also pointed out that Nigeria officers commit to their organization because of economic reasons, rather than having affection for the police department or work, contributing to the widespread problem of police corruption (Aremu et al, 2011).…”
Section: Predicting Organizational Commitment Among Police Officersmentioning
confidence: 99%
“…Two studies found significant positive relationships between EI and officer job performance, even when controlling for important factors like cognitive abilities and personality traits (Al Ali et al, 2012;Gbadeyan et al, 2017). Similarly, another study found a significant positive relationship between EI and readiness to combat crime (Ayinde and Ayegun, 2018). Only one study examined whether EI could be related to reduced misconduct behaviors in police officers.…”
Section: Impact Of Emotional Intelligence On Police Officersmentioning
confidence: 99%
“…Table 1 reports a citation, research setting, method, sample description, EI-specific research question, EI measure and EI conceptual model for each of the studies screened into our review. We initially attempted to report the year of data collection for each study, but this information was only included in three papers (Arnatt and Beyerlein, 2014; Ayinde and Ayegun, 2018; Lokesh et al , 2016), so the decision was made to remove the column from the table. We identified 20 studies conducted in 9 countries.…”
Section: Current Studymentioning
confidence: 99%